Confidentiality & consent in police custody: General principles. (July 2018) - Payne-James, Jason
Abstract: The care of detainees (prisoners) in police custody has had much focus in recent years. The nature of the role of the doctor or other healthcare professionals within the police custodial setting may often be subject to conflicts, but their respective duties as healthcare professionals should generally overide any police or forensic issue that may be relevant. The laws or rules or statute that govern doctor, nurse or paramedic practice may vary from country to country, but the broad principles of healthcare ethics are universal and have been formulated not only by national healthcare regulatory bodies but by international organizations such as the World Medical Association. This article discusses in particular the duties of consent and confidentiality within the police custodial setting, giving examples of where conflicts may arise, and how they should be dealt with. Highlights: The duties of a healthcare professional to detainees in police custody are the same as to any other patient in any other setting. Duties of consent and confidentiality are key to the relationship between healthcare professional and detainee. There are times when dual obligations to patient and police (or other legal bodies) may conflict. Every healthcare professional should be aware of statute, policy or guidance which apply locally should such conflicts be encountered.